2018
DOI: 10.1080/15548627.2018.1535292
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose induces autophagy via lysosomal-mediated TFEB activation in models of motoneuron degeneration

Abstract: Macroautophagy/autophagy, a defense mechanism against aberrant stresses, in neurons counteracts aggregate-prone misfolded protein toxicity. Autophagy induction might be beneficial in neurodegenerative diseases (NDs). The natural compound trehalose promotes autophagy via TFEB (transcription factor EB), ameliorating disease phenotype in multiple ND models, but its mechanism is still obscure. We demonstrated that trehalose regulates autophagy by inducing rapid and transient lysosomal enlargement and membrane perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
228
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(253 citation statements)
references
References 84 publications
13
228
1
Order By: Relevance
“…This finding suggests that Treh1b maintains cellular homeostasis through trehalose hydrolysis and plays important physiological roles in lysosomes. Consistent with this observation, recent studies have demonstrated trehalose-regulated autophagy through a mechanism related to changes in lysosomes (Rusmini & Cortese, 2018). Our data suggest that selectively driven subcellular adaptation played an important role in the functional diversification of duplicate Treh gene.…”
Section: Discussionsupporting
confidence: 90%
“…This finding suggests that Treh1b maintains cellular homeostasis through trehalose hydrolysis and plays important physiological roles in lysosomes. Consistent with this observation, recent studies have demonstrated trehalose-regulated autophagy through a mechanism related to changes in lysosomes (Rusmini & Cortese, 2018). Our data suggest that selectively driven subcellular adaptation played an important role in the functional diversification of duplicate Treh gene.…”
Section: Discussionsupporting
confidence: 90%
“…The natural disaccharide trehalose enhances TFEB nuclear translocation by inducing limited lysosomal membrane enlargement. It activates protein phosphatase-3 CB (PP3CB), calcineurin, and translocates TFEB into the nucleus, independent of inhibiting mTOR activity [169][170][171][172][173][174]. Trehalose treatment enhances the plaque clearance in APP/PS1 mice, and it reduces the tangle formation in P301S mice, again, independent of mTOR [170,171,173].…”
Section: Tfeb-activating Aggrephagy Inducersmentioning
confidence: 99%
“…Several compounds activating the autophagic cascade have been shown to reduce α‐syn toxicity in cellular and animal models . Interesting results have been obtained by using trehalose, a disaccharide able to activate autophagy processes and regulate the activity of TFEB, the main transcriptional regulator of the coordinated lysosomal expression and regulation network . The therapeutic effects of trehalose have been demonstrated in several in vitro and in vivo models of PD and other neurodegenerative diseases .…”
Section: The Alp As a Possible Therapeutic Target For Pdmentioning
confidence: 99%
“…129 Interesting results have been obtained by using trehalose, a disaccharide able to activate autophagy processes [130][131][132] and regulate the activity of TFEB, the main transcriptional regulator of the coordinated lysosomal expression and regulation network. 133,134 The therapeutic effects of trehalose have been demonstrated in several in vitro and in vivo models of PD and other neurodegenerative diseases. 110,133,[135][136][137][138][139][140] Hoffman and colleagues showed that exposure of H4 cells and primary neurons to trehalose, before α-syn exposure, prevents lysosomal enlargement and formation of massive α-syn aggregates.…”
Section: The Alp As a Possible Therapeuticmentioning
confidence: 99%